2014
DOI: 10.1186/s12870-014-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNAs related to salt stress in broccoli, using high-throughput sequencing and bioinformatics analysis

Abstract: BackgroundMicroRNAs (miRNAs) are a new class of endogenous regulators of a broad range of physiological processes, which act by regulating gene expression post-transcriptionally. The brassica vegetable, broccoli (Brassica oleracea var. italica), is very popular with a wide range of consumers, but environmental stresses such as salinity are a problem worldwide in restricting its growth and yield. Little is known about the role of miRNAs in the response of broccoli to salt stress. In this study, broccoli subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…miR159 and miR169 showed same expression patterns in root and shoot, studies have revealed that miR169 is responsive to abiotic stress such as drought, cold and salinity in different species (Ding et al, 2009;Li et al, 2013;Tian et al, 2014;Zhang et al, 2012). miR397 and miR398 also showed same expression levels in root and shoot.…”
Section: Discussionmentioning
confidence: 81%
“…miR159 and miR169 showed same expression patterns in root and shoot, studies have revealed that miR169 is responsive to abiotic stress such as drought, cold and salinity in different species (Ding et al, 2009;Li et al, 2013;Tian et al, 2014;Zhang et al, 2012). miR397 and miR398 also showed same expression levels in root and shoot.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, in keeping with the designation of these miRNAs in other brassica species ( e.g. broccoli [46] ; A. lyrata miRBase Release 21 ), we will name these miRNAs as miR825-5p (22 nt, formerly miR825*) and miR825-3p (21 nt, formerly miR825)…”
Section: Resultsmentioning
confidence: 99%
“…MiR825-5p is conserved in Brassicaceae ( Fig. 1; [43, 46]). Using miR825-5p to search for potential target genes in the B. oleareacea genome in a recently created web browser (https://plantsmallrnagenes.science.psu.edu/ ; [77]), we found that several of its predicted targets, which display sequence similarity to Arabidopsis TNL genes, do accumulate significant amounts of 21 nt siRNAs, supporting the potential conservation of miR825-5p TNL regulatory network among Brassicaceae ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our study, many miRNAs have a similar expression profile under salt stress in some species, but were regulated differently in other species. For example, miR160 levels were downregulated in the inflorescences of rice (Barrera-Figueroa et al 2012), B. juncea (Bhardwaj et al 2014), broccoli (Tian et al 2014) and S. europaea (Feng et al 2015) during salt stress, but upregulated in radish (Sun et al 2015) and H. caspica (Yang et al 2015). Similarly, miR390 was upregulated in Caragana intermedia (Zhu et al 2013), poplar (Populus tremula; Jia et al 2009), broccoli (Tian et al 2014), and radish (Sun et al 2015), but downregulated in B. juncea (Bhardwaj et al 2014).…”
Section: Discussionmentioning
confidence: 99%